Fuzzy Adaptive Compensation Control for Uncertain Building Structural Systems by Sliding-Mode Technology - Houyao Zhu; Zicong Chen; Jianhui Wang; Yunchang Huang; Wenli Chen; Zheng Huang; Huaqi Zhao (Complexity)
Earthquake is a kind of natural disaster, which will have a great impact on the building structure. In the vibration control field of building structures, the timeliness of system stability is extremely important. In traditional control methods, the timeliness is not paid enough attention for systems with uncertain seismic waves. For setting this problem, fuzzy adaptive compensation control for uncertain building structural systems by sliding-mode technology is proposed. It is combined with fuzzy adaptive control and sliding-mode control to ensure that the system can be stable with satisfied timeliness. Also, saturation function is used to ensure the feasible physical implementation of the control system. Compared with the traditional LQR (linear quadratic regulator) control, the simulation results showed that the proposed method can make the system reach a stable state with rapid convergence performance and has a feasible physical implementation.